Implementasi Penggunaan Modul Praktek PLC CP1E Pada Pelajaran Produktif Kompetensi Pengontrolan Motor Listrik Pada Program Keahlian Teknik Ketenagalistrikan SMK Negeri 3 Sorong Provinsi Papua Barat - alexander Jamlean; Markus Tobi (Electro Luceat, 2020)
PLC control is basically a computer designed to replace a relay-based system. SMK Negeri 3 Sorong as one of the Vocational High Schools in Sorong-West Papua has an Electricity Engineering Expertise Program that studies PLC mastery competencies, but from observations made by researchers at SMK Negeri 3 Sorong it turns out that it does not have adequate practice modules in the subject of applying PLC to control of industrial electric motors and there are also difficulties for teachers in these schools in providing learning competency in electric motor control techniques, especially in terms of application or practice. The implementation of the module that will be designed and applied is a learning medium that will help the process of practicing skills in electric motor control engineering competencies automatically using the PLC Omron CP1E module. This module is designed to pay attention to several important things as follows: (1). Practice module in accordance with existing competency standards, (2). Easy to use, and (3). Helps the level of understanding of teachers and students in applying it. This practical module is also used to study the working principle parts of the up / down motor control system with the addition of a simulation module of the lift motor work system using a limit switch that detects the presence of the lift box. At the PLC output, a motor power window and lift indicator are used which indicate the lift box is automatically running.